Perfil epidemiológico em uma Unidade de Terapia Intensiva Neonatal na Região da Amazônia brasileira - Cínthia Kanazawa Silveira; Letícia Maris Camargos Brasil; Jorne Vinícius Cordeiro Cerqueira; Pedro di Tárique Barreto Crispim; Aline Simone Dantas Carvalho (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: To trace the epidemiological profile of newborns admitted to a Neonatal Intensive Care Unit in a region of the Brazilian Amazon. METHODS: Data were collected from 234 newborns admitted to the Neonatal Intensive Care Unit of our department between June 15, 2019 and June 15, 2020. RESULTS: The data pointed to a prevalence of males with adequate weight for gestational age, with main diagnosis upon admission being that of respiratory tract comorbidity and prematurity. In 57.03% of the blood cultures there was no bacterial growth, and when there was growth, coagulase-negative Staphylococcus was present in 20.27%. The death rate calculated in the period was 19.74%. Regarding the mothers, 52.36% had six or more prenatal consultations, 73.39% had cesarean section and 32.76% had diabetes and/or hypertension. CONCLUSION: The findings from this study corroborate the literature, demonstrating a high rate of death and cesarean delivery, with possibly preventable causes with better maternal-fetal care during prenatal consultations, as assessed in the neonatal near miss. More studies concerning the epidemiological profile in Neonatal Intensive Care Units in the northern region are needed because of the scarcity and insufficiency of epidemiological data in this region, which makes it difficult to develop public actions aimed at improving the quality of care provided in Neonatal Intensive Care Units.